Ephemeral Activism: Un/Making Images of Dissent - Altomonte, Jenna Ann (Street Art & Urban Creativity, 2023)
Along the Annexation Wall in Bethlehem, an entangled web of tags, slogans, graphic stencils, and gestures cover the surface of the concrete barrier wall and asphalt road. In Napoli, Italy, similar messages, and symbols appear on the dressed stone facade of government buildings, churches, and apartments. Messages exclaim: Not only Floyd, Iyad Hallaq Too, IAW, Palestino, and No Balls? #Build Walls. Varying in opacity, the words and symbols fight for legibility and presence, acting as a conversational message board between local and international activists. Such visual elements are, according to Ella Chmielewska, “connected with the specific history of protest, contestation, and subversion framed by the locality” (Chmielewska, 2007). Thus, graffiti may be read as an actual and symbolic act of resistance, framed by locality. Considering the saturation of solidarity-based graffiti in places like Bethlehem and Napoli, this paper examines how urban space both facilitates and complicates the durability of activist-based interventions. Through a pictorial study, I focus on the effects of graffiti-based activism and examine how these marks continue to draw attention to solidarity-based causes. Kevin D. Murphy and Sally O’Driscoll refer to these types of marks as “ephemeral interventions,” a reference to the temporary nature of graffiti and the potential long-term impact of certain politically motivated works that produce iconic symbols/signs (Murphy and O’Driscoll, 2015). Whether along the Annexation Wall in Bethlehem or the streets of Napoli, graffitied messages are specific to local political and social causes, yet also connect to greater, global solidarity movements.